Cartoons and collaboration in wartime China: the mobilization of Chinese cartoonists under Japanese occupation - Taylor, Jeremy E. (SAGE Publications, 2015)
The work of Chinese cartoonists who published their illustrations in the popular press in occupied China from 1937 to 1945 has largely escaped the attention of scholars of both the occupation itself and the broader field of cartoon history. This article seeks to fill this gap in the literature by analyzing how the very nature of the occupation, together with efforts undertaken by collaborationist governments such as that of Wang Jingwei, created a context in which a particular body of artists could continue to draw. In so doing, the article raises questions about the place of “collaborationist” cartoonists in the broader development of art and propaganda in China and about the very nature of collaboration in the Chinese context.